A prototype of Candidate Selection System (CSS) for Angkatan Tentera Malaysia (ATM) / Adnan Mohd - Mohd, Adnan (Faculty of Information Technology and Quantitative Sciences, 2005)
This Candidates Selection System (CSS) is built to select Candidates for Angkatan Tentera Malaysia (ATM). This system allow user to get information about latest news, change log in password and check the status of applicant. The targets of this system are for diploma, bachelor and master holders that range of age not over than 27 years old. This system is focused to the selection of Candidates that request job from ATM. After the selection process. Candidates and Officers can print the selection result. This system is built as a web-based system that can be access online. This system also is developed using combination of waterfall model and evolutionary prototyping. ASP is used as programming language; MS Access is selected as database and Internet Information Services (IIS) as Web server. Hopefully this system will aid Officers in Selection and Candidates in Registration process.